If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-c+7=1
We move all terms to the left:
-c+7-(1)=0
We add all the numbers together, and all the variables
-1c+6=0
We move all terms containing c to the left, all other terms to the right
-c=-6
c=-6/-1
c=+6
| 2w=6w-72 | | (2x+156)-4x=(4x+192)-4x | | 64=2^n+9 | | 6c+14=—5c+4+9c | | 154=h^2+3h | | 2c-33=c | | 22-4m=6 | | 4=2f-4 | | 6x-85+x+28=5x-6 | | 3.5n=-45.5 | | 2p-17=5p-77 | | 20x+15x^2=0 | | 9+5m=8m | | 1/2b+4=1/2b+88 | | 32(x+2.32)=114.24 | | 2v-40=v | | 12.833333333333=h^2+h | | 3k+145=271 | | 2x2x-4=3x-6 | | 3=1+2q | | 135xX=15 | | 5=t/0 | | -53+4k=11 | | 4z+7z=-20-1 | | 4z-56+3z=99 | | 9x-2(x+5)=2x-(4-x)-12 | | -10x-8=-58 | | 4,99=z-5,01 | | 3(6+x)=34 | | 5c+6+4c-24+6c-16+2c+20=360 | | 38.5=(h+3)(h) | | 2a•3,1=12,3 |